No Signs of Neuroinflammation in Women With Chronic Fatigue Syndrome or Q Fever Fatigue Syndrome Using the TSPO Ligand [11C]-PK11195. Issue 1 (January 2022) - Raijmakers, Ruud; Roerink, Megan; Keijmel, Stephan; Joosten, Leo; Netea, Mihai; van der Meer, Jos; Knoop, Hans; Klein, Hans; Bleeker-Rovers, Chantal; Doorduin, Janine
Abstract : Background and Objectives: The pathophysiology of chronic fatigue syndrome (CFS) and Q fever fatigue syndrome (QFS) remains elusive. Recent data suggest a role for neuroinflammation as defined by increased expression of translocator protein (TSPO). In the present study, we investigated whether there are signs of neuroinflammation in female patients with CFS and QFS compared with healthy women, using PET with the TSPO ligand 11 C-( R )-(2-chlorophenyl)- N -methyl- N -(1-methylpropyl)-3-isoquinoline-carbox-amide ([ 11 C]-PK11195). Methods: The study population consisted of patients with CFS (n = 9), patients with QFS (n = 10), and healthy subjects (HSs) (n = 9). All subjects were women, matched for age (±5 years) and neighborhood, aged between 18 and 59 years, who did not use any medication other than paracetamol or oral contraceptives, and were not vaccinated in the last 6 months. None of the subjects reported substance abuse in the past 3 months or reported signs of underlying psychiatric disease on the Mini-International Neuropsychiatric Interview. All subjects underwent a [ 11 C]-PK11195 PET scan, and the [ 11 C]-PK11195 binding potential (BPND ) was calculated. Results: No statistically significant differences in BPND were found for patients with CFS or patients with QFS compared with HSs. BPND of [ 11 C]-PK11195 correlated with symptom severity scores in patients with QFS, but a negative correlation was found in patients with CFS. Discussion: In contrast to what was previously reported for CFS, we found no significant difference in BPND of [ 11 C]-PK11195 when comparing patients with CFS or QFS with healthy neighborhood controls. In this small series, we were unable to find signs of neuroinflammation in patients with CFS and QFS. Trial Registration Information: EudraCT number 2014-004448-37.